The Influence of Entrepreneurship Knowledge and The Family Environment on the Interest of Entrepreneurship Students in Business Administration Faculty of Social and Legal Science University Makassar State University - Syamsuriani, Syamsuriani; Aslinda, Andi; Baharuddin, Aris (Pinisi Business Administration Review, 2023)
This study aims to determine the effect of entrepreneurial knowledge and family environment on the entrepreneurial interest of students in Business Administration, Makassar State University. This study uses quantitative research methods with data collection techniques through observation and questionnaires. The number of samples used were 80 students of the business administration study program. The results of this study use data analysis consisting of validity test, reality test, descriptive data analysis technique and inferential data analysis using SPSS 25 application.The results of this study show that each indicator of the entrepreneurial knowledge variable is in the very good category, the busty family environment is in the very good category, and interest in entrepreneurship is in the very good category. Then from the results of the partial test (T test) there is a partial effect of entrepreneurial knowledge and family environment on interest in entrepreneurship, then from the results of the simultaneous test (F test) there is a simultaneous influence of entrepreneurial knowledge and family environment on interest in entrepreneurship. Then the results of the multiple correlation test show a strong/high relationship between the three variables. The results of the coefficient of determination show how entrepreneurial knowledge and the family environment have a strong enough contribution in influencing entrepreneurial interest in Business Administration students, Faculty of Social Sciences and Law, Makassar State University.